Human thrombopoietin: gene structure, cDNA sequence, expression, and chromosomal localization. - Foster, D C (1994)
Thrombopoietin (TPO), a lineage-specific cytokine affecting the proliferation and maturation of megakaryocytes from committed progenitor cells, is believed to be the major physiological regulator of circulating platelet levels. Recently we have isolated a cDNA encoding a ligand for the murine c-mpl protooncogene and shown it to be TPO. By employing a murine cDNA probe, we have isolated a gene encoding human TPO from a human genomic library. The TPO locus spans over 6 kb and has a structure similar to that of the erythropoietin gene (EPO). Southern blot analysis of human genomic DNA reveals a hybridization pattern consistent with a single gene locus. The locus was mapped by in situ hybridization of metaphase chromosome preparations to chromosome 3q26-27, a site where a number of chromosomal abnormalities associated with thrombocythemia in cases of acute myeloid leukemia have been mapped. A human TPO cDNA was isolated by PCR from kidney mRNA. The cDNA encodes a protein with 80% identity to previously described murine TPO and is capable of initiating a proliferative signal to murine interleukin 3-dependent BaF3 cells expressing the murine or human TPO receptor.